2017
DOI: 10.1186/s13075-017-1253-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the HLA-DRβ1 third hypervariable region amino acid sequence according to charge and parental inheritance in systemic sclerosis

Abstract: BackgroundSpecific HLA class II alleles are associated with systemic sclerosis (SSc) risk, clinical characteristics, and autoantibodies. HLA nomenclature initially developed with antibodies as typing reagents defining DRB1 allele groups. However, alleles from different DRB1 allele groups encode the same third hypervariable region (3rd HVR) sequence, the primary T-cell recognition site, and 3rd HVR charge differences can affect interactions with T cells. We considered 3rd HVR sequences (amino acids 67–74) irres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It corresponds with our findings that DRB1*0101 is a protective allele for GD and that DRB1*1502 has a tendency to decrease the risk of GD. Although how charges and polarities promote or impede the binding of thyroid antigens to pocket conformations have not been fully elucidated, it has been found in studies of type 1 diabetes, Sjögren's syndrome, systemic sclerosis and Hashimoto's thyroiditis(HT) that the polarity and charge of amino acids on the DRb chain could promote or avoid disease progression [4,32,40,41]. A study of the relationship between HLA-DR pockets and HT found that DRb1-Arg74, in contrast to protective DRb1-Glu74, creates a narrower pocket that makes the thyroid peptide more susceptible to binding to the T-cell receptor, which leads to autoimmune thyroiditis [39].…”
Section: Mechanisms By Which Hla-drb1 Alleles Can Affect To Gdmentioning
confidence: 99%
“…It corresponds with our findings that DRB1*0101 is a protective allele for GD and that DRB1*1502 has a tendency to decrease the risk of GD. Although how charges and polarities promote or impede the binding of thyroid antigens to pocket conformations have not been fully elucidated, it has been found in studies of type 1 diabetes, Sjögren's syndrome, systemic sclerosis and Hashimoto's thyroiditis(HT) that the polarity and charge of amino acids on the DRb chain could promote or avoid disease progression [4,32,40,41]. A study of the relationship between HLA-DR pockets and HT found that DRb1-Arg74, in contrast to protective DRb1-Glu74, creates a narrower pocket that makes the thyroid peptide more susceptible to binding to the T-cell receptor, which leads to autoimmune thyroiditis [39].…”
Section: Mechanisms By Which Hla-drb1 Alleles Can Affect To Gdmentioning
confidence: 99%
“…One of the most extensive studies enrolling 1300 SSc patients and 1000 controls with Caucasian, African, and Hispanic American backgrounds found that the associated HLA class II alleles were different among ethnic groups, and all associations were not robust [ 94 ]. The associations between susceptibility of SSc and the third hypervariable region (HVR) sequences of the DRB1 gene were also investigated but were again borderline [ 95 ]. On the other hand, the HLA region (6p21.3), especially the HLA-DPB1 and DPB2 , was consistently identified as the gene region most strongly associated with SSc by GWAS, and this association was most prominent in SSc patients with anti-topo I antibody [ 45 ], but it remains controversial if the primarily associated genes were located within HLA or non-HLA genes.…”
Section: Roles Of Hla Gene Polymorphisms In Ssc Susceptibilitymentioning
confidence: 99%
“…Several studies have determined the contribution of HLA Class II molecules to the development of SSc. The charge of amino acid motifs at the 67–74 position on the third hypervariable region of HLA-DRB1 affected their association with SSc [ 17 ]. The uncharged polar residue tyrosine at 30, and amino acid sequence of 71 TRAELDT 77 on the first domain of the HLA-DQ β chain have been reported in SSc patients, being anti-topoisomerase antibody (ATA) positive [ 18 ].…”
Section: Introductionmentioning
confidence: 99%